Effects of a sedentary behaviour intervention in emergency dispatch centre phone operators: a study protocol for the SECODIS randomised controlled cross-over trial - Bruno Pereira; Frederic Dutheil; Jeannot Schmidt; Martial Mermillod; Jean-Baptiste Bouillon-Minois; Marion Trousselard; Daniel Pic; Maëlys Clinchamps; Thierry Taillandier (BMJ Open)
Introduction Sedentary behaviour is a public health problem. We mainly have sedentary behaviour at work, transforming them into occupational risk. To our knowledge, there is no intervention study on the reduction of occupational sedentary behaviour in a real work situation and its impact on health and biomarkers of stress. The main objective is to study changes in sedentary behaviour following a behavioural intervention (sit-and-stand desk and cycle ergometer).Methods and analysis This is a randomised controlled trial in cross-over design conducted in a single centre. The study will be proposed to emergency medical dispatchers of Clermont-Ferrand. Each volunteer will be followed during three cycles of 1 week (3 weeks in total). Each 1-week cycle is made up of 12 hours of work (three conditions: a control and two interventions), 12 hours of successive rest and 6 days of follow-up. For each condition, the measurements will be identical: questionnaire, measure of heart rate variability, electrodermal activity and level of physical activity, saliva and blood sampling. The primary outcome is sedentary behaviour at work (ie, number of minutes per day standing/active). Data will be analysed with both intention-to-treat and per protocol analysis. A p<0.05 will be considered as indicating statistical significance.Ethics and dissemination The study protocol has been approved by the Ethics Committee Ouest IV, FRANCE. The study is registered in ClinicalTrials.gov. All patients will be informed about the details of the study and sign written informed consent before enrolment in the study. Results from this study will be published in a peer-reviewed journal. This study involves human participants and was approved by Comité de protection des personnes Ouest IVCPP reference: 23/132-2National number: 2022-A02730-43.Trial registration number NCT05931406.